Proposal for improving the cutting process in a poultry slaughterhouse: a case study in an industry in Espírito Santo - Carvalho, Flavio Lucio Santos de; Christ, Jackson Simon (Brazilian Journal of Production Engineering, 2021)
The great competitiveness between organizations made them look for more efficient ways to increase their productivity and reduce their losses. Thus, it is essential to know the activities that add and do not add value to the process and the product. It is equally important to implement process improvements and increases in costs and revenues, eliminating or reducing task losses. Therefore, the study has as its objective a proposal for improvement in a certain stage of the process of a poultry slaughterhouse. For the research, data from the production process of the evaluated company were collected. With the application of the following tools: Value Stream Mapping (VSM) and the Cause and Effect Diagram provided a better analysis of the process, thus obtaining a diagnosis of the real and current situation. Therefore, the proposal for improving the process was prepared with the objective of reducing breast fillet losses, a product that has one of the highest sales values, and better efficiency in the production process.
Keywords: VSM, process, losses, improvement, efficient